Cancel (Out) Emissions? The Envisaged Role of Carbon Dioxide Removal Technologies in Long-Term National Climate Strategies - Buylova, Alexandra; Fridahl, Mathias; Nasiritousi, Naghmeh; Reischl, Gunilla (Frontiers in Climate, 2021)
Carbon dioxide removal (CDR) increasingly features in climate scenarios that hold global warming well below 2°C by 2100. Given the continuous gap between climate mitigation pledges and the emission pathways that are aligned with achieving the temperature goals of the Paris Agreement, we would expect countries to promote CDR in their long-term planning to achieve mid-century targets. Yet, countries may not consider it their responsibility to contribute to the global response to climate change using CDR. Thus, a study of the respective country's long-term climate plans is both timely and vital. Such a study could reveal the pledged collective ambition, the contribution of CDR to the pledged ambition, and how the envisaged role of CDR is described by the different countries. This paper explores the long-term low emission development strategies (LT-LEDS) of countries in order to map the role of CDR in addressing climate change. We also supplement our examination of strategies with the opinions of climate experts. Based on an inductive coding of the material and a literature review, the analytical focus of the analysis includes CDR targets and planning, types of CDR, barriers and opportunities to CDR implementation, as well as international cooperation. Our study of 25 national LT-LEDS submitted to the UN or to the EU, as well as 23 interviews with climate experts, shows that national plans for CDR vary substantially across countries and are generally lacking in detail. The findings also demonstrate that CDR is perceived to be necessary and desirable for achieving mid-century climate goals, but also reveal variation in the intended role of CDR. We use an interpretive approach to outline three possible visions of CDR in climate action: as a panacea, as a necessary fallback and as a chimera. We conclude by discussing what our findings of the envisaged roles of CDR in addressing climate change mean for climate governance. This research thereby contributes to the literature on governing CDR with new comprehensive insights into the long-term climate strategies of countries.